Khat chewing and its associated factors among pregnant women in Chiro district, eastern Ethiopia: a community-based study - Geremew, Habtamu; Kebede, Fekadu Abera; Negash, Abraham; Mengstie, Misganaw Asmamaw; Geremew, Demeke (Frontiers in Psychiatry, 2023)
Introduction: Despite its deleterious consequences, khat chewing is escalating worldwide.However, there is a lack of evidence about the extent of khat chewing among pregnant women in Ethiopia, particularly in the current study area. Therefore, this study aimed to assess the prevalence of current khat chewing and its associated factors among pregnant women in Chiro district, eastern Ethiopia.Methods: This community-based cross-sectional study was conducted in Chiro district from November 1 to 30, 2022 G.C. Study participants were selected using the systematic random sampling technique. An interview-administered structured questionnaire was used to collect data through a house-to-house survey. The data were entered into EpiData version 3.1 and analyzed in STATA 14 software. Characteristics of study participants were summarized using descriptive analysis, and binary logistic regression was used to identify determinants of khat chewing.Results: A total of 409 pregnant women participated in this study, with a response rate of 99%.